Faktor-Faktor Penentu Pertumbuhan Ekonomi: Analisis Konsep, Indikator, Dan Pendekatan Pengukuran - Fahrudin , Fahrudin (PT. Sharia Journal and Education Center, 2024)
Abstract Economic growth is a crucial indicator reflecting the ability of an economy to produce goods and services. This article examines various factors influencing economic growth and relevant measurement methods. Utilizing data from Gross Domestic Product (GDP) and Gross Regional Domestic Product (GRDP), the article explains how economic growth is measured and the indicators used to assess changes in economic output. The primary focus is on three key factors affecting economic growth: capital accumulation, population growth, and technological advancement. Additionally, the article discusses various approaches to calculating GRDP, including the production, income, and expenditure approaches. By providing a comprehensive understanding of these factors and related indicators, this article aims to offer valuable insights for determining priority sectors in regional development and strategies for fostering sustainable economic growth. Keywords: Economic Growth, Gross Domestic Product (GDP), Gross Regional Domestic Product (GRDP), Capital Accumulation Abstrak Pertumbuhan ekonomi adalah indikator penting yang mencerminkan kapasitas suatu perekonomian dalam menghasilkan barang dan jasa. Artikel ini mengkaji berbagai faktor yang mempengaruhi pertumbuhan ekonomi serta metode pengukuran yang relevan. Dengan menggunakan data Produk Domestik Bruto (PDB) dan Produk Domestik Regional Bruto (PDRB), artikel ini menjelaskan bagaimana pertumbuhan ekonomi diukur dan indikator yang digunakan untuk mengevaluasi perubahan dalam output ekonomi. Fokus utama artikel ini adalah pada tiga faktor kunci yang mempengaruhi pertumbuhan ekonomi: akumulasi modal, pertumbuhan populasi, dan kemajuan teknologi. Selain itu, artikel ini membahas berbagai pendekatan dalam perhitungan PDRB, termasuk pendekatan produksi, pendapatan, dan pengeluaran. Dengan pemahaman yang mendalam mengenai faktor-faktor ini dan indikator terkait, artikel ini bertujuan untuk memberikan wawasan yang berguna bagi penentuan sektor prioritas dalam pembangunan regional serta strategi yang dapat diterapkan untuk mendorong pertumbuhan ekonomi yang berkelanjutan. Kata Kunci: Pertumbuhan Ekonomi, Produk Domestik Bruto (PDB), Produk Domestik Regional Bruto (PDRB), Akumulasi Modal